Isolasi dan Aplikasi Fungi Entomopatogen dari Larva Nyamuk Aedes aegypti L. - Wuri Artikasari; Emantis Rosa; Bambang Irawan (Jurusan Biologi FMIPA Universitas Cenderawasih, 2019)
DHF (Dengue Hemorrhagic Fever) is a serious problem in Indonesia. DHF disease control has been applied so far, one of which is the use of larvacide temephos (abate). However larvacide is a chemical insecticide that has a negative impact on human health and causes resistance. Therefore in this research, biological control is carried out by utilizing entomopathogenic fungi as a larvacide. The purpose of this study was to determine the effectiveness of entomopathogenic fungi isolated from Ae aegypti larvae. Against the death of Ae. Aegypti mosquito larvae with the moist chamber method. This study used a completely randomized design (CRD) with a factorial pattern and performed two repetitions. Factor A is a type of fungi with 3 levels, namely A1: Aspergillus sp1, A2: Aspergillus sp2, and A3: Syncephalastrum sp. Factor B is a dilution with 7 levels, namely B0: Control, B1: 100 (without dilution), B2: 10-1, B3: 10-2, B4: 10-3, B5: 10-4, B6: 10-5 with every treatment was applied in 2 repetitions. Observations were made 24 hours after treatment for 3 days. Data were analyzed using analysis of variances (anova) and continued with the Least Significant Difference Test (LSD) at 5%. The results indicate that fungi isolates are the most effective in killing Ae. Aegypti mosquito larvae is Aspergillus sp1 and Aspergillus sp2 on the treatment of spores without dilution. Key words: DHF; larvacide; Aedes aegypti; Entomopathogenic Fungi.